Mount Sinai expert guides. - Oh, William K.; Chari, Ajai (Mount Sinai expert guides., 2019)
"Covering the entire spectrum of this fast-changing field, Diagnostic Imaging: Oncology, second edition, is an invaluable resource for radiologists and surgical and medical oncologists -- anyone who requires an easily accessible, highly visual reference covering cancer imaging and staging. A team of renowned experts in radiology, oncology, and body imaging provide carefully updated information and an abundance of high-quality images throughout, making this edition a useful learning tool as well as a handy reference for daily practice. Provides nearly 3,000 annotated images including full-color graphics for each cancer stage. Updated TNM and grading tables from the new American Joint Committee on Cancer (AJCC) Staging Manual and updated WHO classifications. New chapters covering radiological staging of tumors recently introduced in the AJCC 8th edition and new chapter divisions that reflect the current AJCC staging system. Provides practical, easy-to-find details on routes of spread, imaging techniques, suggestions for treatment based on tumor stages identified in a patient's imaging studies, and extensive imaging examples of a variety of cancers in many different stages. Begins each chapter with updated TNM staging tables from the AJCC followed by full-color graphic depictions of TNM criteria. Uses bulleted, succinct text for quick comprehension of essential information, as well as a consistent chapter format offering an Overview, Relevant Pathology, Imaging Findings, Clinical Issues, Reporting Checklist, and Selected References." -- Provided by publisher.